MODERN VIEWS ON THE TREATMENT OF PATIENTS WITH DIABETIC FOOT SYNDROME: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Sattarov, I.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
There is a significant increase in the number of patients with diabetes mellitus (DM). Thus, according to experts from the World Health Organization (WHO), about 422 million people are suffering from DM in the world, and by 2040, the number of people with this disease will reach 642 million. This pathology leads to the development of various complications, one of which is diabetic foot syndrome (DFS), which occurs among 15% of patients with DM. The problem of prevention and treatment of DFS is relevant since this disease worsens the quality of life of patients and leads to their disability. In addition, the risk of limb amputation increases. Thus, 15-70% are performed on patients with DM out of the total number of amputations.